Exploring how PRIME-Parkinson care is implemented and whether, how and why it produces change, for who and under what conditions: a protocol for an embedded process evaluation within the PRIME-UK randomised controlled trial - Yoav Ben-Shlomo; Sabi Redwood; Judi Kidger; Emma Tenison; Heather Brant; Emily J Henderson; Fiona Lithander; Katherine Lloyd; Safi Smith (BMJ Open)
Introduction The PRIME-UK randomised controlled trial (RCT) aims to establish whether a model of care that seeks to be proactive, integrated and empower participants, caregivers and healthcare professionals can improve outcomes in people with parkinsonism. Given that this intervention is novel and complex, understanding whether and how the intervention will be acceptable, implementable, cost-effective and scalable across contexts are key questions beyond that of whether ‘it works’. We describe an embedded process evaluation to answer these questions, which aims to support interpretation of the trial results, refinement of the intervention and support future scaling of the PRIME-Parkinson model of care.Methods and analysis A mixed-methods approach will be used to collect data across four process evaluation domains: implementation, mechanism of change, acceptability and context. Quantitative data will be collected prospectively from all participants and analysed descriptively with exploratory tests of relationships as power allows. Qualitative data will be collected through semistructured interviews with a purposively sampled subpopulation of participants, caregivers and staff members as well as case studies where relevant. Interview transcripts will be analysed thematically using interpretive qualitative analysis. Synthesis of quantitative and qualitative data will also be performed to draw conclusions.Ethics and dissemination The quantitative data will be collected as part of the main PRIME-UK RCT which was been granted NHS REC approval (21/LO/0387) on 27 July 2021. The qualitative data will be collected as part of a substudy, ‘PRIME-Qual’, which was granted NHS REC approval (21/LO/0388) on 14 July 2021. The mixed-methods process evaluation will be published after the conclusion of the trial in addition to the main trial findings.Trial registration number NCT05127057.